Additive for producing water-soluble quantum dot, water-soluble quantum dot dispersion, and composite quantum dot

JP2025035911APending Publication Date: 2025-03-14NIPPON CHEMICAL IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023143252
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、水性溶媒中で安定であり、量子収率に優れた水溶性量子ドット製造用の添加剤、この添加剤を使用した水溶性量子ドット分散液、及び水溶性量子ドットと添加剤からなる複合量子ドットを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035911000008
    Figure 2025035911000008
  • Figure 2025035911000009
    Figure 2025035911000009
  • Figure 2025035911000010
    Figure 2025035911000010
Patent Text Reader

Abstract

To provide an additive for producing water-soluble quantum dots, with which water-soluble quantum dots exhibiting an excellent quantum yield and excellent stability even in an aqueous solvent such as water can be obtained; a water-soluble quantum dot dispersion in which the water-soluble quantum dots are dispersed in an aqueous solvent; and composite quantum dots comprising the water-soluble quantum dots and the additive.SOLUTION: An additive for producing water-soluble quantum dots comprises a phosphine compound represented by the following formula (1), (2), (3), (4), or (5) (where, each R is independently selected from a hydroxyalkyl group, an aminoalkyl group, a mercaptoalkyl group, or a cyanoalkyl group, each having 1-8 carbon atoms).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an additive for producing water-soluble quantum dots, a water-soluble quantum dot dispersion using the additive, and a composite quantum dot comprising a water-soluble quantum dot and the additive. [Background technology]

[0002] In recent years, the development of quantum dots as luminescent materials has progressed. Cadmium-based quantum dots such as CdSe, CdTe, and CdS are being developed as representative quantum dots due to their excellent luminescence properties. In addition, since cadmium is highly toxic and has a high environmental impact, the development of cadmium-free quantum dots such as InP, CuInS2, and ZnTeSe is expected.

[0003] Since quantum dots have a unique size of nanoparticles, it is necessary to stabilize them by suppressing particle aggregation and defects on the particle surface in order to maintain excellent luminescence properties. Ligands present on the particle surface play a major role in stabilizing quantum dots, and various methods have been considered. For example, Patent Document 1 describes that semiconductor nanocrystals (quantum dots) can be obtained by stirring a reaction mixture containing an inert solvent, a cationic precursor, an anionic precursor, and a surface stabilizing ligand at a specific temperature range, and describes that the nanocrystals are stabilized by using a first ligand and a second ligand as the surface stabilizing ligand.

[0004] Additionally, Patent Documents 2 and 3 use phosphine-based ligands to stabilize quantum dots, while Patent Document 4 uses multidentate ligands obtained by oligomerizing phosphine-based ligands. Furthermore, Patent Document 5 describes that by combining fluorescent semiconductor nanoparticles (quantum dots) with a stabilizing additive made of a phosphine-based compound, it is possible to improve dispersibility in a carrier fluid and prevent photodecomposition or thermal decomposition of the nanoparticles.

[0005] In the manufacture of quantum dots, non-aqueous organic solvents such as toluene and octane are generally used because of the ease of reaction control and preparation of quantum dots, the stability of the obtained quantum dots, and the high quantum yield, etc. The techniques described in Patent Documents 1 to 5 aim to achieve stabilization in non-aqueous organic solvents, but depending on the application, quantum dots dispersed in an aqueous solvent are required.

[0006] Regarding the development of quantum dots that can be dispersed in aqueous solvents, i.e., water-soluble quantum dots, methods are being considered that utilize the excellent luminescence properties of quantum dots to measure biological substances such as proteins, viruses, and nucleic acids by using molecular recognition bodies bound to molecular recognition substances. In order to use quantum dots as marker substances in vivo, it is necessary to make the quantum dots water-soluble by coating the quantum dot surface with water-soluble ligands, but such treatment poses problems such as stability and reduced quantum yield. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2010 / 083431 Brochure [Patent Document 2] International Publication No. 2007 / 095061 Brochure [Patent Document 3] JP 2010-9995 A [Patent Document 4] International Publication No. 2004 / 042784 Brochure [Patent Document 5] International Publication No. 2017 / 048608 Brochure Summary of the Invention [Problem to be solved by the invention]

[0008] To make quantum dots water-soluble, it is necessary to make the ligands present on the quantum dot surface have hydrophilic functional groups, but since the hydrophilic functional groups are easily changed in water, it is thought that this has a negative effect on the stability and quantum yield of quantum dots. In other words, if the behavior of the hydrophilic functional groups in water can be stabilized, it will be possible to achieve excellent stability and quantum yield even for water-soluble quantum dots, and the development of water-soluble quantum dots will progress.

[0009] Therefore, an object of the present invention is to provide an additive for producing water-soluble quantum dots that has excellent stability even in an aqueous solvent such as water and can produce water-soluble quantum dots with excellent quantum yield, a water-soluble quantum dot dispersion in which the water-soluble quantum dots are dispersed in an aqueous solvent, and a composite quantum dot consisting of the water-soluble quantum dots and the additive. [Means for solving the problem]

[0010] As a result of intensive research to solve the above problems, the inventors discovered that the presence of a reducing compound in the vicinity of a hydrophilic functional group can suppress the oxidation of the functional group, and that the coordination of a specific reducing compound to the surface of a quantum dot increases the stability of the quantum dot itself, which leads to the stability of the quantum dots in water and suppresses the decrease in quantum yield, and thus completed the present invention.

[0011] That is, the present invention provides an additive for producing water-soluble quantum dots, which contains a phosphine compound represented by the following formula (1), (2), (3), (4) or (5).

[0012] [ka] (In the formula, each R independently represents a hydroxyalkyl group, an aminoalkyl group, a mercaptoalkyl group, or a cyanoalkyl group having 1 to 8 carbon atoms.)

[0013] The present invention also provides a water-soluble quantum dot dispersion comprising water-soluble quantum dots, the additive, and water.

[0014] The present invention also provides a composite quantum dot comprising a water-soluble quantum dot and the additive. Effect of the Invention

[0015] According to the present invention, it is possible to provide an additive for producing water-soluble quantum dots that is stable in an aqueous solvent and has an excellent quantum yield, a water-soluble quantum dot dispersion using this additive, and a composite quantum dot consisting of a water-soluble quantum dot and the additive. [Brief description of the drawings]

[0016] [Figure 1] 1 shows an emission spectrum of the water-soluble quantum dot aqueous dispersion obtained in Example 1. [Diagram 2] 1 shows an emission spectrum of the water dispersion of water-soluble quantum dots obtained in Example 2. [Diagram 3] 1 shows an emission spectrum of an aqueous dispersion of water-soluble quantum dots obtained in Comparative Example 1. [Figure 4] 1 shows an emission spectrum of an aqueous dispersion of water-soluble quantum dots obtained in Comparative Example 2. [Diagram 5] FIG. 13 is a graph showing the change in fluorescence intensity over time measured in a light irradiation resistance test of the aqueous dispersion of water-soluble quantum dots obtained in Example 10. [Figure 6] FIG. 13 is a graph showing the change in fluorescence intensity over time measured in a light irradiation resistance test of the aqueous dispersion of water-soluble quantum dots obtained in Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The additive for producing water-soluble quantum dots of the present invention (hereinafter simply referred to as the "additive") is used for producing water-soluble quantum dots and contains a phosphine compound represented by the following general formula (1), (2), (3), (4) or (5). [ka] (In the formula, each R independently represents a hydroxyalkyl group, an aminoalkyl group, a mercaptoalkyl group, or a cyanoalkyl group having 1 to 8 carbon atoms.)

[0018] As the alkyl group of the hydroxyalkyl group, aminoalkyl group, mercaptoalkyl group or cyanoalkyl group having 1 to 8 carbon atoms represented by R in the general formulas (1), (2), (3), (4) and (5), from the viewpoint of enabling the additive of the present invention to be stably present in the vicinity of the hydrophilic ligand, preferred examples thereof include linear or branched alkyl groups, and specific examples thereof include methyl, ethyl, n-propyl, n-butyl, 2-methylpropyl, n-pentyl, n-hexyl, n-heptyl and n-octyl.

[0019] Examples of linear or branched hydroxyalkyl groups having 1 to 8 carbon atoms include hydroxymethyl, 2-hydroxyethyl, 3-hydroxypropyl, 4-hydroxybutyl, 5-hydroxypentyl, 6-hydroxyhexyl, 7-hydroxyheptyl, 8-hydroxyoctyl, and 3-hydroxy-2-methylpropyl groups. Examples of linear or branched aminoalkyl groups having 1 to 8 carbon atoms include aminomethyl, 2-aminoethyl, 3-aminopropyl, 4-aminobutyl, 5-aminopentyl, 6-aminohexyl, 7-aminoheptyl, 8-aminooctyl, and 3-amino-2-methylpropyl groups. Examples of the linear or branched mercaptoalkyl group having 1 to 8 carbon atoms include a mercaptomethyl group, a 2-mercaptoethyl group, a 3-mercaptopropyl group, a 4-mercaptobutyl group, a 5-mercaptopentyl group, a 6-mercaptohexyl group, a 7-mercaptoheptyl group, an 8-mercaptooctyl group, and a 3-mercapto-2-methylpropyl group. Examples of the linear or branched cyanoalkyl group having 1 to 8 carbon atoms include a cyanomethyl group, a 2-cyanoethyl group, a 3-cyanopropyl group, a 4-cyanobutyl group, a 5-cyanopentyl group, a 6-cyanohexyl group, a 7-cyanoheptyl group, an 8-cyanooctyl group, and a 3-cyano-2-methylpropyl group. Among these, from the viewpoint of allowing the additive of the present invention to be stably present in the vicinity of a hydrophilic ligand, a linear hydroxyalkyl group having 1 to 8 carbon atoms, preferably 1 to 5 carbon atoms, is preferred.

[0020] In the general formula (1), the Rs may be the same or different. Examples of the phosphine compound represented by the general formula (1) include compounds in which R is a hydroxyalkyl group, an aminoalkyl group, a mercaptoalkyl group, or a cyanoalkyl group having 1 to 8 carbon atoms, preferably 1 to 5 carbon atoms. Among these, from the viewpoint of being present in the vicinity of a hydrophilic ligand and contributing to the stabilization of the water-soluble quantum dot, it is preferable that R is the same and is a hydroxyalkyl group having 1 to 5 carbon atoms. Examples of such phosphine compounds include tris(hydroxymethyl)phosphine, tris(2-hydroxyethyl)phosphine, tris(3-hydroxypropyl)phosphine, tris(4-hydroxybutyl)phosphine, and tris(5-hydroxypentyl)phosphine.

[0021] The phosphine compound represented by the general formula (1) can be produced by a known method. For example, it can be obtained by adding an alkene to a phosphine. The phosphine compound represented by the general formula (1) may be a commercially available product. For example, tris(3-hydroxypropyl)phosphine and the like are available from Nippon Chemical Industry Co., Ltd.

[0022] The phosphine compound represented by the general formula (2) includes a compound in which R is a hydroxyalkyl group, an aminoalkyl group, a mercaptoalkyl group, or a cyanoalkyl group having 1 to 8 carbon atoms, preferably 2 to 6 carbon atoms. Among these, from the viewpoint of being present in the vicinity of a hydrophilic ligand and contributing to the stabilization of a water-soluble quantum dot, R is preferably a hydroxyalkyl group having 2 to 6 carbon atoms. Examples of such a phosphine compound include 1-(hydroxymethyl)phosphorane, 1-(2-hydroxyethyl)phosphorane, 1-(3-hydroxypropyl)phosphorane, 1-(4-hydroxybutyl)phosphorane, and 1-(5-hydroxypentyl)phosphorane.

[0023] The phosphine compound represented by the general formula (2) can be produced by a known method. For example, it can be obtained by an addition reaction between phosphorane and alkene. The phosphine compound represented by the general formula (2) may be a commercially available product.

[0024] The phosphine compound represented by the general formula (3) includes compounds in which R is a hydroxyalkyl group, an aminoalkyl group, a mercaptoalkyl group, or a cyanoalkyl group having 1 to 8 carbon atoms, preferably 2 to 6 carbon atoms. Among these, from the viewpoint of being present in the vicinity of a hydrophilic ligand and contributing to the stabilization of a water-soluble quantum dot, R is preferably a hydroxyalkyl group having 2 to 6 carbon atoms. Examples of such phosphine compounds include 9-(hydroxymethyl)phosphabicyclo[4.2.1]nonane, 9-(2-hydroxyethyl)phosphabicyclo[4.2.1]nonane, 9-(3-hydroxypropyl)phosphabicyclo[4.2.1]nonane, 9-(4-hydroxybutyl)phosphabicyclo[4.2.1]nonane, and 9-(5-hydroxypentyl)phosphabicyclo[4.2.1]nonane.

[0025] The phosphine compound represented by the general formula (3) can be produced by a known method. For example, it can be obtained by subjecting phosphabicyclo[4.2.1]nonane to an addition reaction with an alkene. The phosphine compound represented by the general formula (3) may be a commercially available product.

[0026] The phosphine compound represented by the general formula (4) includes compounds in which R is a hydroxyalkyl group, an aminoalkyl group, a mercaptoalkyl group, or a cyanoalkyl group having 1 to 8 carbon atoms, preferably 2 to 6 carbon atoms. Among these, from the viewpoint of being present in the vicinity of a hydrophilic ligand and contributing to the stabilization of a water-soluble quantum dot, R is preferably a hydroxyalkyl group having 2 to 6 carbon atoms. Examples of such phosphine compounds include 9-(hydroxymethyl)phosphabicyclo[3.3.1]nonane, 9-(2-hydroxyethyl)phosphabicyclo[3.3.1]nonane, 9-(3-hydroxypropyl)phosphabicyclo[3.3.1]nonane, 9-(4-hydroxybutyl)phosphabicyclo[3.3.1]nonane, and 9-(5-hydroxypentyl)phosphabicyclo[3.3.1]nonane.

[0027] The phosphine compound represented by the general formula (4) can be produced by a known method. For example, it can be obtained by subjecting phosphabicyclo[3.3.1]nonane to an addition reaction with an alkene. The phosphine compound represented by the general formula (4) may be a commercially available product.

[0028] The phosphine compound represented by the general formula (5) is a compound in which one of the nitrogen atoms of hexamethylenetetramine is replaced with a phosphorus atom, specifically, 1,3,5-triaza-7-phosphaadamantane. The phosphine compound represented by the general formula (5) can be produced by a known method. For example, it can be obtained by reacting tris(hydroxymethyl)phosphine with hexamethylenetetramine. In addition, the phosphine compound represented by the general formula (5) may be a commercially available product, for example, available from Sigma-Aldrich Co., Ltd.

[0029] The additive for producing water-soluble quantum dots of the present invention is a phosphine compound represented by the general formula (1), (2), (3), (4) or (5), and when the additive is added to an aqueous solvent dispersion of water-soluble quantum dots, the stability of the water-soluble quantum dots in the aqueous solvent becomes excellent. As one of the reasons, the present inventors believe that the behavior of the quantum dots in the aqueous solvent is stabilized because the phosphine compound is present in the vicinity of the hydrophilic functional group coordinated to the surface of the water-soluble quantum dots, and the oxidation is suppressed by the reduction action on the hydrophilic functional group. In addition, as another reason, the present inventors believe that the stability of the quantum dots themselves is increased by the direct coordination of the phosphine compound to the surface of the quantum dots, which leads to the stability of the behavior of the quantum dots in water.

[0030] The water-soluble quantum dot additive of the present invention can be used as a water-soluble quantum dot dispersion liquid by being composed of an aqueous solvent and water-soluble quantum dots. The aqueous solvent includes water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, dimethylsulfoxide, and tetrahydrofuran, among others. In view of the possibility of use in vivo utilizing the characteristics of the aqueous medium, water is particularly preferable. The water-soluble quantum dots can be produced, for example, by the following process.

[0031] First, hydrophilic ligands are added to the hydrophobic quantum dot dispersion, and the ligands bonded to the surface of the quantum dots are exchanged for hydrophilic ligands to obtain hydrophilic quantum dots (ligand exchange step). Next, the hydrophilic quantum dots are dispersed in an aqueous solvent to obtain an aqueous solvent dispersion of hydrophilic quantum dots (dispersion step). Next, a surface treatment agent is added to the aqueous solvent dispersion to perform surface treatment of the hydrophilic quantum dots in the aqueous solvent, and an aqueous solvent dispersion of surface-treated hydrophilic quantum dots is obtained (surface treatment step). Finally, a shell-forming agent is added to the aqueous solvent dispersion of the surface-treated hydrophilic quantum dots to form a shell on the surface of the surface-treated hydrophilic quantum dots to obtain an aqueous solvent dispersion of water-soluble quantum dots.

[0032] The additive of the present invention is believed to suppress the oxidation of the hydrophilic functional group of the ligand by being present in the vicinity of the hydrophilic ligand bound to the surface of the hydrophilic quantum dot, and to improve the stability of the quantum dot in water by being directly coordinated to the surface of the quantum dot. Therefore, it is preferable to use it after the ligand exchange process, and for example, by adding it in the surface treatment process or adding it to the aqueous solvent dispersion of the water-soluble quantum dot, water-soluble quantum dots that are stable in aqueous solvents and have excellent quantum yield can be obtained. Each step of producing the water-soluble quantum dots will be described below.

[0033] <Hydrophobic quantum dot dispersion> The hydrophobic quantum dot dispersion liquid is a liquid in which hydrophobic quantum dots are dispersed in a solvent, and the hydrophobic quantum dots are quantum dots having hydrophobic ligands on their surfaces. The hydrophobic quantum dot dispersion liquid may be obtained by reacting raw material compounds consisting of elements constituting the hydrophobic quantum dots in a solvent, or may be a liquid in which commercially available hydrophobic quantum dots are dispersed in a solvent.

[0034] The solvent of the dispersion liquid is preferably a non-polar organic solvent, more preferably a solvent made of an aliphatic hydrocarbon. Examples of the aliphatic hydrocarbon include saturated hydrocarbons such as n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-dodecane, n-hexadecane, and n-octadecane; and unsaturated aliphatic hydrocarbons such as 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene. The aliphatic hydrocarbon used as the solvent may be one type, or two or more types may be mixed together.

[0035] Examples of the quantum dots constituting the hydrophobic quantum dots include cadmium-based quantum dots such as CdSe, CdTe, and CdS, and cadmium-free quantum dots such as InP, CuInS, and ZnTeSe. In the present invention, the quantum dots are preferably of a core-shell structure in which a shell is formed on the surface of a core, and are particularly preferably of a core-shell structure in which the core has at least an InP-based quantum dot obtained by reacting a phosphorus source with an indium source, and the shell has a coating compound other than an InP-based compound.

[0036] Examples of the hydrophobic ligand that constitutes the hydrophobic quantum dots include carboxylic acid derivatives, phosphine derivatives, amine derivatives, and phosphonic acid.

[0037] The carboxylic acid derivative is preferably one in which the alkyl group in the molecule is linear and has 2 to 24 carbon atoms. Specific examples of carboxylic acids in which the alkyl group in the molecule is linear and has 2 to 24 carbon atoms include capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, elaidic acid, oleic acid, linolenic acid, and erucic acid. Among these, from the viewpoint of improving the quality of the obtained hydrophobic quantum dots, those in which the alkyl group in the molecule has 12 to 20 carbon atoms are particularly preferred, and oleic acid is the most preferred.

[0038] The phosphine derivative is preferably a primary to tertiary alkylphosphine, and the alkyl group in the molecule is preferably a straight chain having 2 to 18 carbon atoms. The alkyl groups in the molecule may be the same or different. Specific examples of the alkyl phosphine having a straight chain alkyl group having 2 to 18 carbon atoms include monoethylphosphine, monobutylphosphine, monodecylphosphine, monohexylphosphine, monooctylphosphine, monododecylphosphine, monohexadecylphosphine, diethylphosphine, dibutylphosphine, didecylphosphine, dihexylphosphine, dioctylphosphine, didodecylphosphine, dihexadecylphosphine, triethylphosphine, tributylphosphine, tridecylphosphine, trihexylphosphine, trioctylphosphine, tridodecylphosphine, and trihexadecylphosphine. Among these, from the viewpoint of improving the quality of the obtained hydrophobic quantum dots, those in which the number of carbon atoms in the alkyl group in the molecule is 4 to 12 are particularly preferred, those which are trialkylphosphines are preferred, and trioctylphosphine is most preferred.

[0039] The amine derivative is preferably a primary to tertiary alkylamine, and preferred examples thereof include linear alkylamines in which the alkyl group in the molecule has 2 to 18 carbon atoms, and aromatic alkylamines in which the alkyl group has 6 to 12 carbon atoms. The alkyl groups in the molecule may be the same or different. Specific examples of linear alkylamines in which the alkyl group has 2 to 18 carbon atoms include monoethylamine, monobutylamine, monodecylamine, monohexylamine, monooctylamine, monododecylamine, monohexadecylamine, diethylamine, dibutylamine, didecylamine, dihexylamine, dioctylamine, didodecylamine, dihexadecylamine, triethylamine, tributylamine, tridecylamine, trihexylamine, trioctylamine, tridodecylamine, and trihexadecylamine. Specific examples of aromatic alkylamines in which the alkyl group has 6 to 12 carbon atoms include aniline, diphenylamine, triphenylamine, monobenzylamine, dibenzylamine, tribenzylamine, naphthylamine, dinaphthylamine, and trinaphthylamine. The phosphonic acid is preferably a monoalkylphosphonic acid in which the alkyl group in the molecule is a straight-chain alkyl group having from 2 to 18 carbon atoms.

[0040] When the hydrophobic quantum dots used in the present invention have a core-shell structure, examples of coating compounds suitable for the shell include Al2O3, Ga2O3, SiO2, CdS, CdSe, CdSeS, CdTe, CdSeTe, CdTeS, ZnS, ZnSe, ZnSeS, ZnTe, ZnSeTe, ZnTeS, ZnO, ZnOS, ZnSeO, and ZnTeO, etc. In the present invention, it is preferable that the coating compound is obtained by reaction with at least a zinc source.

[0041] The hydrophobic quantum dot dispersion used in the present invention can be produced by a known method, for example, the method described in JP-A-2023-033157.

[0042] <Ligand exchange process> The ligand exchange reaction is a process in which hydrophilic ligands are added to a hydrophobic quantum dot dispersion liquid, and the ligands bonded to the surfaces of the quantum dots are exchanged for hydrophilic ligands to obtain hydrophilic quantum dots.

[0043] Examples of hydrophilic ligands include thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, selenols, phosphites, phosphinic acids, phosphonic acids, phosphoric acids, phosphine oxides, phosphine sulfides, phosphine selenides, carboxylic acids, thiol-containing carboxylic acids, thiocarboxylic acids, thionocarboxylic acids, dithiocarboxylic acids, sulfenic acids, sulfinic acids, and sulfonic acids. Among these, from the viewpoint of stability and improvement of quantum yield of hydrophilic quantum dots, thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, phosphonic acids, carboxylic acids, and thiol-containing carboxylic acids are preferred, and thiol-containing carboxylic acids are particularly preferred.

[0044] Examples of the thiol-containing carboxylic acid include thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, cysteine, acetylcysteine, homocysteine, penicillamine, etc. Among these, from the viewpoint of improving the water dispersibility and quantum yield of the quantum dots, thioglycolic acid, 3-mercaptopropionic acid, cysteine, and acetylcysteine ​​are preferred, and 3-mercaptopropionic acid is more preferred.

[0045] The temperature when adding hydrophilic ligands to the quantum dot dispersion is preferably 0°C to 350°C, more preferably 20°C to 300°C, and the treatment time is preferably 1 minute to 600 minutes, more preferably 5 minutes to 240 minutes. The amount of the ligand to be added depends on the type of the ligand, but is preferably 0.01 g / L to 100,000 g / L, more preferably 0.1 g / L to 2,000 g / L, relative to the reaction solution containing the quantum dots.

[0046] The atmosphere when adding the hydrophilic ligand to the quantum dot dispersion liquid is preferably a non-oxidizing atmosphere such as an inert gas atmosphere, reduced pressure, or vacuum, from the viewpoint of preventing the denaturation of the quantum dots and the by-production of oxides. From the viewpoint of ease of operation, the non-oxidizing atmosphere is preferably an inert gas atmosphere such as nitrogen gas or argon gas. Through the above steps, a dispersion liquid containing hydrophilic quantum dots is obtained.

[0047] Next, the hydrophilic quantum dots are separated from the dispersion liquid containing the hydrophilic quantum dots. Examples of the separation method include common methods such as centrifugation, decantation, and suction filtration. At this time, in order to remove unnecessary hydrophobic ligands, it is preferable to add a solvent capable of dissolving the ligands and repeat the operation of separating the hydrophilic quantum dots by centrifugation or the like several times. Through the above steps, hydrophilic quantum dots are obtained.

[0048] <Dispersion process> The dispersion step is a step of dispersing the hydrophilic quantum dots in an aqueous solvent to obtain an aqueous solvent dispersion of the hydrophilic quantum dots.

[0049] The aqueous solvent is not particularly limited as long as it is a water-soluble solvent, and examples thereof include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, with water being preferred.

[0050] The hydrophilic quantum dot aqueous solvent dispersion is obtained by dispersing the hydrophilic quantum dots in the aqueous solvent. The hydrophilic quantum dots can be dispersed in the aqueous solvent as they are, but for example, when the hydrophilic ligand is a carboxylic acid containing a thiol, from the viewpoint of obtaining a uniform dispersion, it is preferable to react these with sodium hydroxide, potassium hydroxide, ammonia water, tetraethylammonium hydroxide, etc., to convert the carboxyl group into a salt form, and then disperse in the aqueous solvent, and more preferably to convert into an ammonium salt form and then disperse in the aqueous solvent.

[0051] In addition, since the hydrophilic quantum dots before the dispersion process may contain by-products or unreacted impurities, they may be subjected to a purification process. This purification process can be performed by adding an organic solvent such as methanol, ethanol, 2-propanol, acetone, acetonitrile, or tetrahydrofuran to a solution containing hydrophilic quantum dots to precipitate the hydrophilic quantum dots, separating the solution containing impurities from the hydrophilic quantum dots, and dispersing the separated hydrophilic quantum dots in an aqueous solvent. The solution containing impurities and the hydrophilic quantum dots can be separated by operations such as centrifugation, decantation, and suction filtration.

[0052] One of the preferred methods of using the additive of the present invention is to add it in the dispersion process. By adding the additive of the present invention in the dispersion process, the additive can be easily arranged close to the hydrophilic quantum dots, so that the quantum yield and stability of the water-soluble quantum dots can be easily improved. The amount of additive added depends on the type, but is preferably 10 molecules or more and 1,000,000 molecules or less, more preferably 100 molecules or more and 100,000 molecules or less, per quantum dot particle in the hydrophilic quantum dot aqueous solvent dispersion.

[0053] The number of quantum dot particles can be determined, for example, by the following method. The average particle diameter r of each of the core and the core / shell is determined by transmission electron microscope measurement, and the shape is calculated by 4 / 3πr 3 The volume of the core is calculated by the radius of the shell, 4 / 3πr.3 The volume is calculated by subtracting the volumes of the core and shell inside from the volume calculated above. The calculated core and shell volumes are multiplied by the density of their constituent materials to convert them into mass, and these are added together to calculate the mass m of one core / shell quantum dot particle. In addition, the concentration of each element that makes up the core / shell quantum dot is quantified by ICP measurement to calculate the total mass M of quantum dots contained in 1 ml of solution. The quantum dot concentration (number of particles / ml) is calculated by dividing the total mass M per ml by the mass m per particle, and the number of particles is calculated from the quantum dot concentration and the volume of the quantum dot solution.

[0054] The method of adding the additive in the dispersion step is not particularly limited, and it may be added to the hydrophilic quantum dot aqueous solvent dispersion. That is, the method of directly adding the additive and the method of adding the additive in a state of being dissolved or dispersed in a solvent are included. The solvent when adding the additive in a state of being dissolved or dispersed in a solvent is not particularly limited as long as it is a water-soluble solvent, and examples thereof include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, but water is particularly preferred. Through the above steps, an aqueous solvent dispersion of hydrophilic quantum dots is obtained.

[0055] <Surface treatment process> The surface treatment step is a step of adding a surface treatment agent to the aqueous solvent dispersion to perform surface treatment of the hydrophilic quantum dots in the aqueous solvent, thereby obtaining an aqueous solvent dispersion of surface-treated hydrophilic quantum dots.

[0056] In the surface treatment step, defects on the quantum dot surface caused by the ligand exchange step are repaired in an aqueous solvent with a surface treatment agent, so that the quantum dots become stable and the surface becomes uniform, enabling stable shell formation in the shell formation step described below. Therefore, the water-soluble quantum dots finally obtained according to the present invention have the same FWHM as the quantum dots obtained in an organic solvent, and the decrease in quantum yield is suppressed.

[0057] Examples of the surface treatment agent include metal halides such as halides of Li, Na, K, Be, Mg, Ca, Sr, Cu, Ag, Au, Hg, In, Sn, Pb, Zn, Cd, Al, and Ga; hydrogen halides such as HF, HCl, HBr, and HI; nitrogen halides such as NF3; halides of quaternary ammonium compounds and quaternary phosphonium compounds such as NR4F and PR4F (R represents H, or a saturated, unsaturated, or aromatic hydrocarbon having 1 to 8 carbon atoms which may be linear or branched, and which may be substituted with a functional group); carboxylic acids, phosphonic acids, sulfonic acids, and acid halides thereof; and metal carboxylates, metal carbamates, and metal thiocarboxylates containing metals such as Li, Na, K, Be, Mg, Ca, Sr, Cu, Ag, Au, Hg, In, Sn, Pb, Zn, Cd, Al, and Ga. Among these, from the viewpoint of further improving the quantum yield, the surface treatment agent is preferably a metal halide or a metal carboxylate. The metal halide may be zinc fluoride, zinc chloride, zinc bromide, zinc iodide, etc., and zinc chloride is particularly preferred. The metal carboxylate may be zinc acetate, zinc trifluoroacetate, zinc myristate, zinc oleate, zinc benzoate, etc., and zinc acetate is particularly preferred.

[0058] The surface treatment of the hydrophilic quantum dots can be carried out by adding a surface treatment agent to the hydrophilic quantum dot aqueous solvent dispersion. The surface treatment is preferably carried out at a temperature of -20°C or higher and 200°C or lower, more preferably at a temperature of 0°C or higher and 150°C or lower, particularly at a temperature of 20°C or higher and 120°C or lower, and preferably for 1 minute or longer and 600 minutes or shorter, more preferably at a temperature of 5 minutes or longer and 240 minutes or shorter, particularly at a temperature of 10 minutes or longer and 120 minutes or shorter. The amount of the surface treatment agent added depends on the type of the surface treatment agent, but is preferably 0.01 g / L or higher and 10,000 g / L or lower, more preferably 0.1 g / L or higher and 1,000 g / L or lower, relative to the hydrophilic quantum dot aqueous solvent dispersion.

[0059] The atmosphere in the surface treatment step is preferably a non-oxidizing atmosphere such as an inert gas atmosphere, reduced pressure, or vacuum, from the viewpoint of preventing the denaturation of the quantum dots and the by-production of oxides. From the viewpoint of ease of operation, the non-oxidizing atmosphere is preferably an inert gas atmosphere such as nitrogen gas or argon gas.

[0060] The method of adding the surface treatment agent in the surface treatment step includes a method of directly adding the surface treatment agent to the reaction liquid, and a method of adding the surface treatment agent dissolved or dispersed in a solvent to the reaction liquid. When the surface treatment agent is added by a method of adding the surface treatment agent dissolved or dispersed in a solvent to the reaction liquid, the solvent is not particularly limited as long as it is a water-soluble solvent, and examples of the solvent include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, with water being particularly preferred. Through the above steps, an aqueous solvent dispersion of surface-treated hydrophilic quantum dots is obtained.

[0061] One of the preferred methods of using the additive of the present invention is to add it in the surface treatment process. By adding the additive of the present invention in the surface treatment process, the additive can be easily arranged close to the hydrophilic quantum dots, so that the effect of improving the quantum yield of the water-soluble quantum dots can be easily exhibited. The amount of additive added depends on the type, but is preferably 10 molecules or more and 100,000 molecules or less, more preferably 100 molecules or more and 10,000 molecules or less, per quantum dot particle in the hydrophilic quantum dot aqueous solvent dispersion. The method of measuring the number of quantum dot particles is as described above.

[0062] The method of adding the additive in the surface treatment step is not particularly limited, and it may be added to the hydrophilic quantum dot aqueous solvent dispersion in the same manner as the surface treatment agent. That is, the method of directly adding the additive and the method of adding the additive in a state of being dissolved or dispersed in a solvent are included. The solvent when adding the additive in a state of being dissolved or dispersed in a solvent is not particularly limited as long as it is a water-soluble solvent, and examples thereof include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, but water is particularly preferred.

[0063] <Shell formation process> The shell formation step in the present invention is a step of adding a shell forming agent to the aqueous solvent dispersion of the surface-treated hydrophilic quantum dots to form a shell on the surface of the surface-treated hydrophilic quantum dots, thereby obtaining an aqueous solvent dispersion of water-soluble quantum dots.

[0064] The shell-forming agent is preferably a mixture of at least one sulfur source selected from thiols, thiol-containing carboxylic acids, thioureas, thiocarbamates, thiocarbonates, thiocarboxylic acids, thionocarboxylic acids, dithiocarboxylic acids, phosphine sulfides, and sulfides of Li, Na, K, Be, Mg, Ca, and Sr, and zinc carboxylate, zinc nitrate, zinc sulfate, zinc hypochlorite, zinc chlorite, zinc chlorate, zinc perchlorate, zinc bromate, zinc iodate, zinc carbonate, zinc borate, zinc hypophosphite, zinc phosphite, zinc phosphate, zinc trifluoromethanesulfonate, or zinc halide. In particular, from the viewpoint of improving the quantum yield, it is preferable to use a mixture of thiol-containing carboxylic acids as the sulfur source and zinc carboxylate, zinc perchlorate, or zinc halide as the zinc source, and it is particularly preferable to use a mixture of thiol-containing carboxylic acids and zinc halide.

[0065] Examples of the thiol-containing carboxylic acids include thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, cysteine, acetylcysteine, homocysteine, penicillamine, etc. Among these, from the viewpoints of the water dispersibility and quantum yield of the quantum dots, thioglycolic acid, 3-mercaptopropionic acid, cysteine, and acetylcysteine ​​are preferred, and 3-mercaptopropionic acid is more preferred.

[0066] As the zinc halide, zinc fluoride, zinc chloride, zinc bromide and zinc iodide are preferred, and zinc chloride is particularly preferred.

[0067] The shell can be formed by adding a shell-forming agent to the aqueous solvent dispersion of the surface-treated hydrophilic quantum dots. After adding the shell-forming agent, the surface-treated hydrophilic quantum dots are treated at preferably 30° C. to 200° C., more preferably 50° C. to 150° C., particularly 70° C. to 120° C., for preferably 1 minute to 600 minutes, more preferably 5 minutes to 240 minutes, particularly 10 minutes to 120 minutes, to form a shell on the surface of the surface-treated hydrophilic quantum dots.

[0068] The atmosphere in the shell formation step is preferably a non-oxidizing atmosphere such as an inert gas atmosphere, reduced pressure, or vacuum, from the viewpoint of preventing the denaturation of the quantum dots and the by-production of oxides. From the viewpoint of ease of operation, the non-oxidizing atmosphere is preferably an inert gas atmosphere such as nitrogen gas or argon gas.

[0069] The method of adding the shell-forming agent in the shell-forming step includes a method of directly adding the shell-forming agent to the reaction liquid, and a method of adding the shell-forming agent dissolved or dispersed in a solvent to the reaction liquid. When the shell-forming agent is added by a method of adding the shell-forming agent dissolved or dispersed in a solvent to the reaction liquid, the solvent is not particularly limited as long as it is a water-soluble solvent, and examples of the solvent include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, with water being particularly preferred. Through the above steps, an aqueous solvent dispersion of water-soluble quantum dots is obtained.

[0070] The water-soluble quantum dots can be separated from the obtained aqueous solvent dispersion of the water-soluble quantum dots by common methods such as centrifugation, decantation, suction filtration, etc. The obtained water-soluble quantum dots are dispersed again in an aqueous solvent to remove insoluble impurities, thereby obtaining a purified aqueous solvent dispersion of the water-soluble quantum dots.

[0071] One of the preferred methods of using the additive of the present invention is to add it to the finally obtained aqueous solvent dispersion of water-soluble quantum dots. By adding the additive at the end of the process, it becomes easier to exert the effect of improving the stability of the water-soluble quantum dots in water. The amount of additive added depends on the type, but is preferably 10 molecules or more and 1,000,000 molecules or less, more preferably 100 molecules or more and 100,000 molecules or less, per quantum dot particle in the hydrophilic quantum dot aqueous solvent dispersion. The method of measuring the number of quantum dot particles is as described above.

[0072] The method of adding the additive is not particularly limited, and examples thereof include a method of directly adding the additive and a method of adding the additive in a state of being dissolved or dispersed in a solvent. When adding the additive in a state of being dissolved or dispersed in a solvent, the solvent is not particularly limited as long as it is a water-soluble solvent, and examples thereof include water, methanol, ethanol, 2-propanol, ethylene glycol, propylene glycol, acetone, acetonitrile, N-methylpyrrolidone, dimethylformamide, and tetrahydrofuran, with water being particularly preferred.

[0073] In this manner, by using the additive of the present invention in the production of water-soluble quantum dots, it is possible to obtain water-soluble quantum dots having excellent stability and excellent quantum yield.

[0074] In addition, the water-soluble quantum dot additive of the present invention functions as a composite quantum dot in combination with a water-soluble quantum dot, and improves stability in an aqueous solvent, i.e., storage stability over time and light resistance. This makes it possible for the composite quantum dot to stably utilize its excellent luminescence function over a long period of time when the quantum dot is used as a marker substance in a living body.

[0075] According to the additive for producing water-soluble quantum dots of the present invention, a water-soluble quantum dot dispersion liquid composed of water-soluble quantum dots and an aqueous solvent can be obtained. Therefore, even if the quantum dots are water-soluble, excellent stability and quantum yield can be achieved, and it is expected that the development of water-soluble quantum dots will progress further. EXAMPLES

[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. The properties in the examples were measured by the following methods. (1) Emission spectrum, maximum fluorescence wavelength, full width at half maximum (FWHM) and quantum yield (PLQY) The obtained aqueous dispersion of quantum dots was measured using an absolute PL quantum yield measurement device (Quantaurus-QY, manufactured by Hamamatsu Photonics KK) under measurement conditions of an excitation wavelength of 400 nm and a measurement wavelength of 200 to 950 nm.

[0077] [Synthesis Example 1] Synthesis of orange InP / ZnSe / ZnS quantum dots 1.43 g of indium myristate was added to 14.25 g of 1-octadecene, and the mixture was heated to 120° C. under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40° C. to obtain a 1-octadecene solution of indium myristate. The obtained 1-octadecene solution of indium myristate was kept at 40° C. under a nitrogen atmosphere, and 2.51 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained.

[0078] Next, the InP quantum dot precursor solution was heated to 280° C. to obtain a reaction solution of InP quantum dots. 7.54g of zinc oleate, 4.09g of zinc chloride, 5.40g of trioctylphosphine selenide, 8.90g of trioctylphosphine, 16.26g of oleylamine, and 16.26g of dioctylamine were mixed in a 200mL reaction vessel, heated to 120°C under reduced pressure with stirring, and degassed for 30 minutes. After degassing, the pressure was returned to atmospheric pressure with nitrogen gas, and the temperature was raised to 180°C under a nitrogen atmosphere, and 18.19g of the reaction solution of InP quantum dots obtained above was added, heated to 230°C and held for 30 minutes, and then further heated to 300°C and held for 60 minutes to obtain an oleylamine / dioctylamine dispersion of InP / ZnSe quantum dots having InP in the core and ZnSe in the shell. After the obtained dispersion was cooled to 240°C, 7.54 g of zinc oleate, 7.54 g of trioctylphosphine, and 4.35 g of trioctylphosphine sulfide were poured thereinto and held for 90 minutes to obtain an oleylamine / dioctylamine dispersion of multi-shell quantum dots having InP in the core and ZnSe and ZnS stacked in the shell.

[0079] After cooling the obtained dispersion to room temperature, 50 g of acetone was added, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 8.67 g of toluene to obtain a toluene dispersion of InP / ZnSe / ZnS quantum dots. 50 g of acetone was further added to this dispersion, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 7.03 g of octane to obtain an octane dispersion of purified InP / ZnSe / ZnS quantum dots. The emission wavelength of the obtained dispersion was 586 nm and showed orange color.

[0080] [Synthesis Example 2] Synthesis of red InP / ZnSe / ZnS quantum dots 1.59 g of indium myristate was added to 14.25 g of 1-octadecene, and the mixture was heated to 120° C. under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40° C. to obtain a 1-octadecene solution of indium myristate. The obtained 1-octadecene solution of indium myristate was kept at 40° C. under a nitrogen atmosphere, and 2.51 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained.

[0081] Next, the InP quantum dot precursor solution was heated to 280° C. to obtain a reaction solution of the base InP quantum dots. In a separate reaction vessel, 2.39 g of indium myristate was added to 21.37 g of 1-octadecene, and the mixture was heated to 120°C under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40°C to obtain a 1-octadecene solution of indium myristate.

[0082] The obtained 1-octadecene solution of indium myristate was kept at 40° C. under a nitrogen atmosphere, and 3.76 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained. The previously prepared base InP quantum dot reaction solution was reheated to 260° C., and the newly prepared InP quantum dot precursor solution was added over 60 minutes to obtain an InP quantum dot reaction solution.

[0083] 7.54g of zinc oleate, 4.09g of zinc chloride, 5.40g of trioctylphosphine selenide, 8.90g of trioctylphosphine, 16.26g of oleylamine, and 16.26g of dioctylamine were mixed in a 200mL reaction vessel, heated to 120°C under reduced pressure with stirring, and degassed for 30 minutes. After degassing, the pressure was returned to atmospheric pressure with nitrogen gas, and the temperature was raised to 180°C under a nitrogen atmosphere, and 15.79g of the reaction solution of InP quantum dots obtained above was added, heated to 230°C and held for 30 minutes, and then further heated to 300°C and held for 60 minutes to obtain an oleylamine / dioctylamine dispersion of InP / ZnSe quantum dots having InP in the core and ZnSe in the shell. After the obtained dispersion was cooled to 240°C, 7.54 g of zinc oleate, 7.54 g of trioctylphosphine, and 4.35 g of trioctylphosphine sulfide were poured thereinto and held for 90 minutes to obtain an oleylamine / dioctylamine dispersion of multi-shell quantum dots having InP in the core and ZnSe and ZnS stacked in the shell.

[0084] After cooling the obtained dispersion to room temperature, 50 g of acetone was added, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 8.67 g of toluene to obtain a toluene dispersion of InP / ZnSe / ZnS quantum dots. 50 g of acetone was further added to this dispersion, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 7.03 g of octane to obtain an octane dispersion of purified InP / ZnSe / ZnS quantum dots. The emission wavelength of the obtained dispersion was 619 nm, and it was red.

[0085] [Synthesis Example 3] Synthesis of yellow InP / ZnSe / ZnS quantum dots 1.20 g of indium myristate was added to 3.56 g of 1-octadecene, and the mixture was heated to 120° C. under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40° C. to obtain a 1-octadecene solution of indium myristate. The obtained 1-octadecene solution of indium myristate was kept at 40° C. under a nitrogen atmosphere, and 2.51 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained.

[0086] Next, the InP quantum dot precursor solution was heated to 250° C. to obtain a reaction solution of InP quantum dots.

[0087] 7.54g of zinc oleate, 4.09g of zinc chloride, 5.40g of trioctylphosphine selenide, 8.90g of trioctylphosphine, 16.26g of oleylamine, and 16.26g of dioctylamine were mixed in a 200mL reaction vessel, heated to 120°C under reduced pressure with stirring, and degassed for 30 minutes. After degassing, the pressure was returned to atmospheric pressure with nitrogen gas, and the temperature was raised to 180°C under a nitrogen atmosphere, and 7.27g of the reaction solution of InP quantum dots obtained above was added, heated to 230°C and held for 30 minutes, and then further heated to 300°C and held for 60 minutes to obtain an oleylamine / dioctylamine dispersion of InP / ZnSe quantum dots having InP in the core and ZnSe in the shell. After the obtained dispersion was cooled to 240°C, 7.54 g of zinc oleate, 7.54 g of trioctylphosphine, and 4.35 g of trioctylphosphine sulfide were poured thereinto and held for 90 minutes to obtain an oleylamine / dioctylamine dispersion of multi-shell quantum dots having InP in the core and ZnSe and ZnS stacked in the shell.

[0088] After cooling the obtained dispersion to room temperature, 50 g of acetone was added, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 8.67 g of toluene to obtain a toluene dispersion of InP / ZnSe / ZnS quantum dots. 50 g of acetone was further added to this dispersion, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 7.03 g of octane to obtain an octane dispersion of purified InP / ZnSe / ZnS quantum dots. The emission wavelength of the obtained dispersion was 551 nm and it was yellow.

[0089] [Synthesis Example 4] Synthesis of green InP / ZnSe / ZnS quantum dots 1.20 g of indium myristate, 0.16 g of zinc myristate, and 0.06 g of zinc acetate were added to 14.25 g of 1-octadecene, and the mixture was heated to 120°C under reduced pressure with stirring and degassed for 1.5 hours. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and cooled to 40°C to obtain a 1-octadecene solution of indium zinc myristate. The obtained 1-octadecene solution of indium zinc myristate was kept at 40° C. under a nitrogen atmosphere, and 2.51 g of a trioctylphosphine solution containing 10% by mass of tris(trimethylsilyl)phosphine was added thereto, and the mixture was held for 10 minutes and then naturally cooled to 20° C. As a result, a yellow liquid containing an InP quantum dot precursor was obtained. Next, the InP quantum dot precursor solution was heated to 250° C. to obtain a reaction solution of InP quantum dots.

[0090] 7.54g of zinc oleate, 4.09g of zinc chloride, 5.40g of trioctylphosphine selenide, 8.90g of trioctylphosphine, 16.26g of oleylamine, and 16.26g of dioctylamine were mixed in a 200mL reaction vessel, heated to 120°C under reduced pressure with stirring, and degassed for 30 minutes. After degassing, the pressure was returned to atmospheric pressure with nitrogen gas, and the temperature was raised to 180°C under a nitrogen atmosphere, and 18.18g of the reaction solution of InP quantum dots obtained above was added, heated to 230°C and held for 30 minutes, and then further heated to 300°C and held for 60 minutes to obtain an oleylamine / dioctylamine dispersion of InP / ZnSe quantum dots having InP in the core and ZnSe in the shell. After the obtained dispersion was cooled to 240°C, 7.54 g of zinc oleate, 7.54 g of trioctylphosphine, and 4.35 g of trioctylphosphine sulfide were poured thereinto and held for 90 minutes to obtain an oleylamine / dioctylamine dispersion of multi-shell quantum dots having InP in the core and ZnSe and ZnS stacked in the shell.

[0091] After cooling the obtained dispersion to room temperature, 50 g of acetone was added, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 8.67 g of toluene to obtain a toluene dispersion of InP / ZnSe / ZnS quantum dots. 50 g of acetone was further added to this dispersion, the mixture was stirred, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected InP / ZnSe / ZnS quantum dots were suspended in 7.03 g of octane to obtain an octane dispersion of purified InP / ZnSe / ZnS quantum dots. The emission wavelength of the obtained dispersion was 539 nm and showed green color.

[0092] [Example 1] (ligand exchange process) 2 ml of the octane dispersion of the orange InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 1 and 10 ml of hexadecane were weighed into a 50 ml two-necked eggplant flask. The mixture was heated to 90°C under reduced pressure while stirring and degassed for 30 minutes. After degassing, the mixture was returned to atmospheric pressure with nitrogen gas and heated to 220°C under a nitrogen atmosphere, 4.0 ml of 3-mercaptopropionic acid was added, and the mixture was held for 10 minutes to obtain InP / ZnSe / ZnS quantum dots in which the ligands were substituted with 3-mercaptopropionic acid. After cooling to 160°C, 40 ml of octane was added and the mixture was cooled to room temperature. The supernatant was removed, 30 ml of hexane was added, and the mixture was stirred, and the supernatant was removed again. This was repeated three times to obtain a solid. The solid was suspended in 5 ml of ethanol, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. (Dispersion process) The recovered InP / ZnSe / ZnS quantum dot precipitate was suspended in 19 ml of pure water and 1 ml of 35% aqueous solution of tetraethylammonium hydroxide, and then insoluble impurities were removed by centrifugation to obtain a purified aqueous dispersion of InP / ZnSe / ZnS quantum dots. (Surface treatment process) 0.028g of anhydrous zinc chloride was dissolved in 0.2ml of pure water to obtain an aqueous solution of anhydrous zinc chloride. 0.1ml of this aqueous solution of anhydrous zinc chloride, 0.1ml of 40% aqueous solution of tris(3-hydroxypropyl)phosphine, 0.5ml of the aqueous dispersion of InP / ZnSe / ZnS quantum dots obtained in the dispersion step, and 1.0ml of pure water were weighed into a glass flask with a lid. After reducing the pressure, the pressure was returned to atmospheric pressure by nitrogen gas to create a nitrogen atmosphere, and the mixture was kept at 40°C for 30 minutes while stirring to obtain an aqueous dispersion of surface-treated InP / ZnSe / ZnS quantum dots. (Shell formation process) To the obtained surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion, 0.1 ml of anhydrous zinc chloride aqueous solution and 0.1 ml of 3-mercaptopropionic acid were added. After reducing the pressure, the pressure was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 60°C and 100°C while stirring under 365 nm UV light irradiation, and after maintaining for 60 minutes, the mixture was cooled to room temperature to obtain a water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was centrifuged to recover a precipitate of water-soluble InP / ZnSe / ZnS quantum dots. The recovered precipitate was dispersed in 0.6 ml of pure water and 0.06 ml of a 35% aqueous solution of tetraethylammonium hydroxide, and then centrifuged to remove insoluble impurities, yielding an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1. The emission spectrum of the obtained aqueous dispersion is also shown in Figure 1.

[0093] [Example 2] A purified aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was obtained by the same procedure as in Example 1, except that the octane dispersion of red InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 2 was used. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1. The emission spectrum of the obtained aqueous dispersion was also measured, and the results are shown in FIG. 2. [Example 3] An aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots was obtained by the same procedure as in Example 1, except that the octane dispersion of yellow InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 3 was used. The emission characteristics of the aqueous dispersion obtained were measured, and the results are shown in Table 1. [Example 4] A purified aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was obtained by the same procedure as in Example 1, except that the octane dispersion of green InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 4 was used. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1.

[0094] [Example 5] (ligand exchange process) 0.10 g of L-cysteine ​​was weighed into a 6 ml glass vial, and 0.8 ml of pure water and 0.25 ml of a 35% aqueous solution of tetraethylammonium hydroxide were added to obtain an L-cysteine ​​aqueous solution. 0.1 ml of the octane dispersion of orange InP / ZnSe / ZnS quantum dots obtained in Synthesis Example 1, 0.5 ml of chloroform, 0.8 ml of pure water, 0.1 ml of 1-butanol, and 0.01 ml of a 40% aqueous solution of tris(3-hydroxypropyl)phosphine were added thereto. The mixture was kept at 40° C. for 4 hours with stirring to obtain a liquid containing solids of InP / ZnSe / ZnS quantum dots in which the ligands were replaced with L-cysteine. (Dispersion process) The solution containing the InP / ZnSe / ZnS quantum dots was washed into a centrifuge tube with 3 ml of 2-propanol, and the InP / ZnSe / ZnS quantum dots were collected as a precipitate by centrifugation. The collected precipitate was suspended in 1.38 ml of pure water and 0.12 ml of a 35% aqueous solution of tetraethylammonium hydroxide, and then insoluble impurities were removed by centrifugation to obtain a purified water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. (Surface treatment process) 0.028g of anhydrous zinc chloride was dissolved in 0.2ml of pure water to obtain an anhydrous zinc chloride aqueous solution. 0.1ml of this anhydrous zinc chloride aqueous solution, 0.1ml of a 40% aqueous solution of tris(3-hydroxypropyl)phosphine, and 0.75ml of the InP / ZnSe / ZnS quantum dot aqueous dispersion obtained in the dispersion step were weighed into a glass flask with a lid. After reducing the pressure, the pressure was returned to atmospheric pressure using nitrogen gas to create a nitrogen atmosphere, and the mixture was kept at 40°C for 30 minutes while stirring to obtain a surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion. (Shell formation process) A suspension of 0.1 ml of anhydrous zinc chloride aqueous solution, 0.10 g of L-cysteine, and 0.3 ml of pure water was added to the obtained surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion. After reducing the pressure, the pressure was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 60°C and 100°C while stirring under 365 nm UV light irradiation, and then the mixture was kept for 60 minutes and cooled to room temperature to obtain a water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was centrifuged to recover the water-soluble InP / ZnSe / ZnS quantum dots as a precipitate. The recovered precipitate was dispersed by adding 0.6 ml of pure water and 0.12 ml of a 35% aqueous solution of tetraethylammonium hydroxide, and then centrifuged to remove insoluble impurities, obtaining an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The luminescence characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1.

[0095] [Example 6] The ligand exchange step and the dispersion step were carried out in the same manner as in Example 1, and an orange InP / ZnSe / ZnS quantum dot aqueous dispersion was obtained. (Surface treatment process) 0.028g of anhydrous zinc chloride was dissolved in 0.2ml of pure water to obtain an aqueous solution of anhydrous zinc chloride. 0.1ml of this aqueous solution of anhydrous zinc chloride, 0.020g of 1,3,5-triaza-7-phosphaadamantane, and 0.5ml of the aqueous dispersion of InP / ZnSe / ZnS quantum dots were weighed into a glass flask with a lid. After reducing the pressure, the pressure was returned to atmospheric pressure using nitrogen gas to create a nitrogen atmosphere, and the mixture was kept at 40°C for 30 minutes while stirring to obtain an aqueous dispersion of surface-treated InP / ZnSe / ZnS quantum dots. (Shell formation process) To the obtained surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion, 0.1 ml of anhydrous zinc chloride aqueous solution and 0.1 ml of 3-mercaptopropionic acid were added. After reducing the pressure, the pressure was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 60°C and 100°C while stirring under irradiation of 365 nm UV light, and then the mixture was kept for 60 minutes and cooled to room temperature to obtain a water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was centrifuged to recover the water-soluble InP / ZnSe / ZnS quantum dots as a precipitate. The recovered precipitate was dispersed in 0.6 ml of pure water and 0.08 ml of a 35% aqueous solution of tetraethylammonium hydroxide, and then centrifuged to remove insoluble impurities, yielding an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The luminescence characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1.

[0096] [Example 7] The ligand exchange step and the dispersion step were carried out in the same manner as in Example 1, and an orange InP / ZnSe / ZnS quantum dot aqueous dispersion was obtained. (Surface treatment process) 0.028g of anhydrous zinc chloride was dissolved in 0.2ml of pure water to obtain an anhydrous zinc chloride aqueous solution. 0.1ml of this anhydrous zinc chloride aqueous solution, 0.020g of tris(hydroxymethyl)phosphine, and 0.5ml of InP / ZnSe / ZnS quantum dot aqueous dispersion were weighed into a glass flask with a lid. After reducing the pressure, the pressure was returned to atmospheric pressure using nitrogen gas to create a nitrogen atmosphere, and the mixture was kept at 40°C for 30 minutes while stirring to obtain a surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion. (Shell formation process) To the obtained surface-treated InP / ZnSe / ZnS quantum dot aqueous dispersion, 0.1 ml of anhydrous zinc chloride aqueous solution and 0.1 ml of 3-mercaptopropionic acid were added. After reducing the pressure, the pressure was returned to atmospheric pressure with nitrogen gas to create a nitrogen atmosphere, and the internal temperature was heated to between 60°C and 100°C while stirring under 365 nm UV light irradiation, and after maintaining for 60 minutes, the mixture was cooled to room temperature to obtain a water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was centrifuged to recover the water-soluble InP / ZnSe / ZnS quantum dots as a precipitate. The recovered precipitate was dispersed by adding 0.6 ml of pure water and 0.04 ml of a 35% aqueous solution of tetraethylammonium hydroxide, and then centrifuged to remove insoluble impurities, obtaining an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The luminescence characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1.

[0097] [Comparative Example 1] The same procedure as in Example 1 was carried out, except that the 40% aqueous solution of tris(3-hydroxypropyl)phosphine was not added in the surface treatment step of Example 1, to obtain an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1. The emission spectrum of the obtained aqueous dispersion was also measured, and the results are shown in FIG. 3.

[0098] [Comparative Example 2] The same procedure as in Example 2 was carried out, except that the 40% aqueous solution of tris(3-hydroxypropyl)phosphine was not added in the surface treatment step of Example 2, to obtain an aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1. Furthermore, the emission spectrum of the obtained aqueous dispersion was measured, and the results are shown in FIG. 4.

[0099] [Comparative Example 3] An aqueous dispersion of purified water-soluble InP / ZnSe / ZnS quantum dots was obtained by the same procedure as in Example 4, except that the 40% aqueous solution of tris(3-hydroxypropyl)phosphine was not added in the surface treatment step of Example 3. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1.

[0100] [Comparative Example 4] A purified aqueous dispersion of water-soluble InP / ZnSe / ZnS quantum dots was obtained by the same procedure as in Example 3, except that the 40% aqueous solution of tris(3-hydroxypropyl)phosphine was not added in the surface treatment step of Example 5. The emission characteristics of the obtained aqueous dispersion were measured, and the results are shown in Table 1.

[0101] [Table 1]

[0102] From the results in Table 1, it can be seen that, although the full width at half maximum of the aqueous dispersion of the same orange water-soluble InP / ZnSe / ZnS quantum dots is the same in Example 1 and Comparative Example 1, the quantum yield of Example 1, in which tris(3-hydroxypropyl)phosphine was added in the surface treatment process, is superior to that of Comparative Example 1. Similarly, in comparisons between Example 2 and Comparative Example 2, Example 3 and Comparative Example 3, and Example 4 and Comparative Example 4, it can be seen that the quantum yield is superior despite the same full width at half maximum. Furthermore, it can be seen that in Example 6, in which 1,3,5-triaza-7-phosphaadamantane, an additive of the present invention, was added, and in Example 7, in which tris(hydroxymethyl)phosphine was added, a higher quantum yield was obtained for the aqueous dispersion of the same orange water-soluble InP / ZnSe / ZnS quantum dots compared to Comparative Example 1, in which the additive of the present invention was not added.

[0103] [Example 8] The dispersion process was carried out in the same manner as in Example 1 to obtain an InP / ZnSe / ZnS quantum dot aqueous dispersion. 0.1 ml of a 40% aqueous solution of tris(3-hydroxypropyl)phosphine was added to the InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion was subjected to evaluation tests for storage stability and pH resistance.

[0104] [Example 9] The dispersion process was carried out in the same manner as in Example 2 to obtain an InP / ZnSe / ZnS quantum dot aqueous dispersion. 0.1 ml of a 40% aqueous solution of tris(3-hydroxypropyl)phosphine was added to the InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion was subjected to evaluation tests for storage stability and pH resistance.

[0105] [Example 10] The dispersion process was carried out in the same manner as in Example 4 to obtain an InP / ZnSe / ZnS quantum dot aqueous dispersion. 0.1 ml of a 40% aqueous solution of tris(3-hydroxypropyl)phosphine was added to the InP / ZnSe / ZnS quantum dot aqueous dispersion. The obtained aqueous dispersion was subjected to evaluation tests for storage stability, pH resistance, and light irradiation resistance.

[0106] [Comparative Example 5] For the InP / ZnSe / ZnS quantum dot aqueous dispersion in Example 8 to which the 40% aqueous solution of tris(3-hydroxypropyl)phosphine had not been added, evaluation tests were carried out on the storage stability and pH resistance.

[0107] [Comparative Example 6] For the InP / ZnSe / ZnS quantum dot aqueous dispersion in Example 9 to which the 40% aqueous solution of tris(3-hydroxypropyl)phosphine had not been added, evaluation tests were carried out on the storage stability and pH resistance.

[0108] [Comparative Example 7] For the InP / ZnSe / ZnS quantum dot aqueous dispersion in Example 10 to which the 40% aqueous solution of tris(3-hydroxypropyl)phosphine had not been added, evaluation tests were carried out on the storage stability, pH resistance, and light irradiation resistance.

[0109] [Comparative Example 8] In Example 8, 0.03 ml of trimethyl phosphate was added to the InP / ZnSe / ZnS quantum dot aqueous dispersion instead of the 40% aqueous solution of tris(3-hydroxypropyl)phosphine. The obtained aqueous dispersion was subjected to evaluation tests for storage stability and pH resistance.

[0110] [Comparative Example 9] In Example 8, 0.02 ml of dimethyl phosphite was added to the InP / ZnSe / ZnS quantum dot aqueous dispersion instead of the 40% aqueous solution of tris(3-hydroxypropyl)phosphine. The obtained aqueous dispersion was subjected to evaluation tests for storage stability and pH resistance.

[0111] [evaluation] (1) Storage stability test For Examples 8 to 10 and Comparative Examples 5 to 9, a storage stability test was carried out. 0.006 ml of the water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion obtained in each Example and Comparative Example was placed in a 2 ml glass vial, and 1.2 ml of pure water was mixed to obtain a test solution. This test solution was left to stand in a cool, dark place at room temperature for one week, and the storage state was visually confirmed thereafter. In addition, the change in luminescence intensity due to irradiation with UV light was visually confirmed. The results are shown in Table 2.

[0112] (2) pH tolerance test Examples 8 to 10 and Comparative Examples 5 to 9 were subjected to a pH resistance test. 0.05 ml of the water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion obtained in each Example and Comparative Example was placed in a 1 ml glass vial, and 2 ml of the dilution solution shown in Table 3 was mixed to obtain a test solution. This was left to stand in a cool, dark place at room temperature for 1 hour, and the storage state thereafter was visually confirmed. In addition, the change in luminescence intensity due to irradiation with UV light was visually confirmed. The results are shown in Table 3.

[0113] (3) Light exposure resistance test Example 10 and Comparative Example 7 were subjected to a light irradiation resistance test. 60 μl of the green water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersions obtained in Example 10 and Comparative Example 7 were placed in a 6 ml glass vial, and 3.0 ml of pure water was mixed to obtain test solutions. 2 The fluorescence intensity of the quantum dots was measured over time and the results are shown in Figures 5 and 6.

[0114] [Table 2]

[0115] [Table 3]

[0116] From the results of the storage stability test in Table 2, it can be seen that each example using the additive of the present invention has excellent storage stability because no precipitate is formed for a long period of time and no change in luminescence intensity is observed. In addition, from the results of the pH resistance test in Table 3, it can be seen that each example using the additive of the present invention has no formation of precipitate and maintains a stable luminescence intensity, so that it can maintain a stable solution state regardless of pH. From the results of the light irradiation resistance test in Figures 5 and 6, it can be seen that the green water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion of Comparative Example 7 shown in Figure 6 shows a decrease in fluorescence intensity, while the green water-soluble InP / ZnSe / ZnS quantum dot aqueous dispersion of Example 10 shown in Figure 5 shows an improvement in light irradiation resistance because the decrease in fluorescence intensity under continuous irradiation with excitation light is suppressed.

Claims

1. An additive for producing water-soluble quantum dots, comprising a phosphine compound represented by the following formula (1), (2), (3), (4) or (5): 【Chemistry 1】 (In the formula, each R independently represents a hydroxyalkyl group, an aminoalkyl group, a mercaptoalkyl group, or a cyanoalkyl group having 1 to 8 carbon atoms.)

2. 2. The additive according to claim 1, wherein R is a hydroxyalkyl group having 1 to 5 carbon atoms.

3. A water-soluble quantum dot dispersion comprising a water-soluble quantum dot, the additive according to claim 1 or 2, and water.

4. The water-soluble quantum dot dispersion according to claim 3 , wherein the additive is disposed adjacent to the water-soluble quantum dots.

5. The water-soluble quantum dots are those in which a ligand selected from thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, phosphonic acids, carboxylic acids, and thiol-containing carboxylic acids is coordinated to the surface of the quantum dots. The water-soluble quantum dot dispersion liquid according to claim 3.

6. A composite quantum dot comprising a water-soluble quantum dot and the additive according to claim 1 or 2.

7. The water-soluble quantum dot is a complex quantum dot having a ligand selected from thiols, amine-containing thiols, amines, alcohols, thiol-containing alcohols, phosphonic acids, carboxylic acids, and thiol-containing carboxylic acids coordinated to the surface of the quantum dot.

Citation Information

Patent Citations

  • Discharge liquid, discharge liquid set, thin film pattern forming method, thin film, light emitting element, image display device, and electronic equipment

    JP2010009995A

  • Stabilized semiconductor nanocrystals

    WO2004042784A2

  • Device including semiconductor nanocrystals and a layer including a doped organic material and methods

    WO2007095061A2

  • Low-temperature synthesis of colloidal nanocrystals

    WO2010083431A1

  • Additive stabilized composite nanoparticles

    WO2017048608A1